O uso do whatsapp como ferramenta de apoio para o ensino e aprendizagem de matemática - GONÇALVES, Rita de Cassia Lobato (2023)
The present paper seeks to make a literature review that deals with problem solving in mathematics classes with the use of social networks, specifically WhatsApp. Methodologically, the work is characterized as a bibliographic study. Thus, the text presents a catalog of works that deal with the theme in the repositories of the Coordination for the Improvement of Higher Education Personnel - CAPES and the Brazilian Digital Library of Theses and Dissertations - BDTD, in a time frame from 2016 to 2021, gathering approximately 50 files, which after filtering were disregarded the duplicate files, those that were not related to the teaching and learning process and the mathematics discipline and those that were not available in full, leaving only two dissertations that were specifically related to the theme. The papers indicated that the use of the application worked positively, leading to reflect that a social network, such as WhatsApp, popularly used by students, favors the teaching of mathematics, becoming a support for the continuity of the classroom dynamics.